Relationship between Vitamin D, Inflammation and Lung Function In Patients with Severe Uncontrolled Asthma - Jovanovska-Janeva, Elena; Dokic, Dejan; Jovkovska-Kaeva, Biserka; Breskovska, Gorica; Goseva, Zlatica; Minov, Jordan; Trajkov, Dejan; Genadieva-Dimitrova, Magdalena; Zafirovska-Ivanovska, Beti (Scientific Foundation SPIROSKI, 2017)
BACKGROUND:Recently epidemiological studies showed that low vitamin D is linked toairway hyperresponsiveness, decreasedlung function, poor asthma control, and steroid–resistant asthma.AIM:We investigatedtherelationshipbetween Vitamin D, inflammation with circulating IL-33 and lung function in 30 patients with severe uncontrolled asthma. MATERIALS AND METHODS:The study included 30 patients with severe uncontrolled asthma. In each of them were measured serum levels of IL-33 and Vitamin D by the ELISA method. The pulmonary function is measuredby basic spirometry parameters, FEV1. The results were statistically elaboratedaccording to the Pearson’s Correlation Tests. RESULTS:The results showed statistically insignificant correlation between Vitamin D and IL-33, and Vitamin D with FEV1 (Vit.D/IL-33; r=0.11323, p=0.551); (Vit.D/FEV1; r=-0.1005; p=0.597) Correlation between IL-33 and FEV1 is negative but statistically significant (IL-33/FEV1; r=-0.5248; p=0.003). CONCLUSION:Because there arelittle studies about the link between vitamin D and asthma, further research toclarify the mechanism how vitamin D control the activity of CD4+ T cells and the related Th2-type cytokines in the parthenogenesis of asthma.
Keywords: asthma; vitamin D; IL-33; FEV1; Th2-type cytokines